Development of libraries of the congress of Southeast Asian librarians. - Yit, Chin Chuan. (2008)
The Congress of Southeast Asian Librarians (CONSAL) has reached its thirtieth year of existence. Meetings were held approximately every three years and the year 2000 was marked for the eleventh CONSAL gathering in Singapore. In support for the event, a study to explore, highlight and identify the development of member countries within the region was undertaken. This study focused on eight aspects of development which were grouped under the categories of physical, standards, systems, staff, collection, user, research and special. A survey was conducted and responses were received from Brunei, Laos, Malaysia, Myanmar, Philippines, Singapore and Vietnam.